O processo de conscientização na sala de aula de língua espanhola - Meneghini, Carla Mayumi [UNESP] (Universidade Estadual de Maringa, 2013)
This article discusses the awareness process of students in a Spanish as a foreign language classroom, at a Centre of Language Studies in a city in the state of São Paulo, Brazil. The frame of reference is Paulo Freire's pedagogy (FREIRE, 1980, 1984, 1987, 1999, 2000), Wallerstein (1983) and Schleppegrell (1997)'s investigations which are important to the comprehension of the relation between Freirean's pedagogy and the language teaching. This is a qualitative research and it focuses on action research practice in a Spanish language classroom, in which a syllabus based on Paulo Freire's pedagogy was implemented in order to verify how the target language was used in the classroom (MENEGHINI, 2001). Data analysis and discussion are based on data triangulation and classroom interactions are taken on primary data. The implementation of this research suggests that the problem posing tasks on themes chosen from the student's realities are the way which leads to the awareness.
The awareness process in a spanish language classroom
Keywords: Freirean's pedagogy; Language use; Problem posing; Qualitative method; Reflection; Spanish language learning/teaching